2020
DOI: 10.3390/ijerph17041343
|View full text |Cite
|
Sign up to set email alerts
|

The Association between the Australian Alcopops Tax and National Chlamydia Rates among Young People—an Interrupted Time Series Analysis

Abstract: A national tax increase, which became known as the “alcopops tax”, was introduced in Australia on the 27th April 2008 on ready-to-drink alcoholic beverages, which are consumed predominantly by young people. The affordability of alcohol has been identified as the strongest environmental driver of alcohol consumption, and alcohol consumption is a well-known risk factor in the spread of sexually transmitted infections via its association with sexual risk-taking. We conducted a study to investigate whether there w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Reducing the alcohol content of the respective drinks, so that less alcohol is consumed with the same fluid intake [54], or increasing the minimum age of consumption from 16 to 18 years could also be effective [55]. Importantly, these beverage-specific, tailored and targeted strategies can have wider benefits across consumption, including broader alcohol consumption levels and links to related outcomes, such as sexually transmitted infections [56] and other harms [57].…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the alcohol content of the respective drinks, so that less alcohol is consumed with the same fluid intake [54], or increasing the minimum age of consumption from 16 to 18 years could also be effective [55]. Importantly, these beverage-specific, tailored and targeted strategies can have wider benefits across consumption, including broader alcohol consumption levels and links to related outcomes, such as sexually transmitted infections [56] and other harms [57].…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol control policies have shown a positive association with reduced STIs in the population , specifically observed for a decrease on the STI's rates when alcohol taxation increased (Gilmore et al, 2020;Staras et al, 2014). These studies suggested indirect casual evidence between alcohol use and STIs.…”
Section: Discussionmentioning
confidence: 95%
“…From these four articles, 28 out of a total of 37 individual estimates, showed a statistically significant inverse association. More recently, studies in the US (Staras et al, 2014) and in Australia (Gilmore et al, 2020) found decreases in gonorrhea and chlamydia rates following an alcohol tax increase. Similarly, a study in the Netherlands (Den Daas et al, 2019) showed an association between increasing the minimum purchasing age and chlamydia rates in the affected age group.…”
Section: Indirect Causal Indicators: Alcohol Policy Interventions And...mentioning
confidence: 99%
“…Six of the studies [8,15,17,[20][21][22] evaluated the effectiveness of an intervention. Of these, two [8,20] found showed a meaningful effect, with only one [8], looking at strategies to reduce the availability and promotion of alcohol on or near university campuses, finding a statistically significant effect.…”
mentioning
confidence: 99%